Mahāṃ-balī yodhā Mahārājā Raṇajīta Siṅgha : prakāsha dhunī shaile wice pahilā Pañjābī nāṭaka - Phul, Gurdial Singh, 1911- (Liṭarecara Hāūsa, 1981)
Play based on the life of Ranjit Singh, Maharaja of Punjab, 1780-1839.